Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/mp.12299
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically guided capsule endoscopy

Abstract: Wireless capsule endoscopy (WCE) is a powerful tool for medical screening and diagnosis, where a small capsule is swallowed and moved by means of natural peristalsis and gravity through the human gastrointestinal (GI) tract. The camera-integrated capsule allows for visualization of the small intestine, a region which was previously inaccessible to classical flexible endoscopy. As a diagnostic tool, it allows to localize the sources of bleedings in the middle part of the gastrointestinal tract and to identify d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 179 publications
0
72
0
Order By: Relevance
“…Other research focuses on the ability to combine the visualization abilities of currently sold capsule systems with therapeutics and better localization abilities. A 2017 review highlights many of the important developments in the field up until the present [104].…”
Section: Robotic Capsules For Diagnostics and Interventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other research focuses on the ability to combine the visualization abilities of currently sold capsule systems with therapeutics and better localization abilities. A 2017 review highlights many of the important developments in the field up until the present [104].…”
Section: Robotic Capsules For Diagnostics and Interventionmentioning
confidence: 99%
“…To investigate potentially less invasive methods, swimming-based and magnetic capsule actuation methods have been developed using liquid stomach distension, see Figure 8-(d) [97]. Early trials reported the use of a handheld magnet to orient a capsule with another magnet inside a water-distended stomach, but these methods are largely nonintuitive to use, leading to the use of robotic methods to reduce fatigue and improve usability/precision [104]. An alternative to the use of moving permanent magnets is electromagnetic coil systems.…”
Section: Capsule Locomotionmentioning
confidence: 99%
See 3 more Smart Citations